Encyclopedia of Membrane Science and Technology 2013
DOI: 10.1002/9781118522318.emst017
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Diffusion Processes

Abstract: The solution‐diffusion model has been widely used to describe solute and solvent transport through high pressure membranes. The main proposition of the theory is that the driving force is a gradient in (electro)chemical potential. This makes the theory applicable to all dense membrane processes because common membrane driving forces such as gradients in temperature, electromotive forces, concentration, and pressure can in fact be translated to (electro)chemical potential gradients. This review describes the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Although the effect of changing permeate flux on salt rejection is clearly observable (49% decline in rejection when the flux was reduced by 22%), the effect is almost insignificant on the rejection of caffeine as a decline of only 5% was measured (at similar flux decline value). Rejection of solutes is expected to increase with increasing flux (or pressure) as the increasing flux has a dilution effect (Verliefde et al, 2013). Figure 2 shows the membrane surface charges (with varying pH) before and after fouling with alginate and latex without the addition of Ca 2+ .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the effect of changing permeate flux on salt rejection is clearly observable (49% decline in rejection when the flux was reduced by 22%), the effect is almost insignificant on the rejection of caffeine as a decline of only 5% was measured (at similar flux decline value). Rejection of solutes is expected to increase with increasing flux (or pressure) as the increasing flux has a dilution effect (Verliefde et al, 2013). Figure 2 shows the membrane surface charges (with varying pH) before and after fouling with alginate and latex without the addition of Ca 2+ .…”
Section: Resultsmentioning
confidence: 98%
“…Based on the solution diffusion model, rejection of solutes is a function of flux (Verliefde et al, 2013). However, other factors also play a role in solute rejection in addition to flux.…”
Section: Relation Between Flux Decline and Solute Rejectionmentioning
confidence: 99%
“…However, it is not clear whether the role of CECP is substantial for NF membranes that poorly reject salts. According to the solution–diffusion model, flux through a membrane increases linearly with applied pressure and solute permeability does not change in dense membranes [ 34 ]. However, solute permeability is independent of the applied pressure and solute concentration.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that hydrophobic compounds may be adsorbed on the hydrophobic membrane surface. However, high rejections due to adsorption are typically only a temporarily effect, until membrane saturation occurs [ 233 ]; then adsorbed molecules may be transported to a higher extent due to their higher partition coefficient [ 234 ]. Reversely, D’haese demonstrated that small hydrophilic organics (such as alcohols) may show negative rejection (up to 4–5 times concentration in the permeate), their transfer being promoted by salting out [ 220 ].…”
Section: Tuning Fo Process To Tackle Current Limitations For Optimmentioning
confidence: 99%